COMPARATIVE ANALYSIS OF EUPHEMISMS IN ENGLISH AND UZBEK (Journal of Universal Science Research, 2025)
This article analyzes euphemisms in English and Uzbek, examining their linguistic structures, functions, and cultural influences. It categorizes them by theme and explores how cultural, religious, and social factors shape their use, enhancing cross-cultural communication and politeness strategies.